2000
DOI: 10.1177/106286060001500104
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to Control of Blood Glucose in Diabetes Mellitus

Abstract: The purpose of this study was to characterize the barriers to tight control of diabetes mellitus. The study collected data from multiple sources at a primary health care clinic in an academic teaching hospital serving an urban population, including patients' charts, structured interviews with patients, a survey of physicians' general perspectives and beliefs concerning diabetes mellitus, and a physician's structured review of barriers to tight control for individual patients. One hundred thirty-five patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
48
0
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(50 citation statements)
references
References 27 publications
1
48
0
1
Order By: Relevance
“…13 Similar findings have also been reported from the USA. [14][15][16][17][18] As attainment of good glycaemic control is critical to improving outcomes in people with diabetes, this qualitative study was conducted to identify and explore barriers to the initiation of insulin therapy in patients with poorly controlled type 2 diabetes who are being prescribed maximum doses of oral medication by MOs in community health centres (CHCs) in the Cape Town metropole. These 44 CHCs are run by the Community Health Services Organisation (CHSO) of the Department of Health of the Provincial Administration of the Western Cape (PAWC) and provide comprehensive primary services for a population of 3 million in the Cape Town metropole.…”
Section: Discussionmentioning
confidence: 99%
“…13 Similar findings have also been reported from the USA. [14][15][16][17][18] As attainment of good glycaemic control is critical to improving outcomes in people with diabetes, this qualitative study was conducted to identify and explore barriers to the initiation of insulin therapy in patients with poorly controlled type 2 diabetes who are being prescribed maximum doses of oral medication by MOs in community health centres (CHCs) in the Cape Town metropole. These 44 CHCs are run by the Community Health Services Organisation (CHSO) of the Department of Health of the Provincial Administration of the Western Cape (PAWC) and provide comprehensive primary services for a population of 3 million in the Cape Town metropole.…”
Section: Discussionmentioning
confidence: 99%
“…35,36 Another concern reported by physicians was that patients do not have a sense of urgency or understanding about treating their diabetes and thus are less likely to adhere to provider recommendations. [35][36][37] Physicians also reported that there was not adequate administrative support for the increased time and effort required to treat diabetic patients. 35,36 Additionally, patient finances were viewed by physicians as a barrier to diabetes care 38 and adequate glycemic control.…”
Section: Physician Attitude Toward Treating Diabetesmentioning
confidence: 99%
“…The success of permanent lifestyle changes is dependent on patients' degree of motivation, psychosocial condition, risk profile and compliance: patient nonadherence to the lifestyle regimen is the most common barrier to care. 29,30 Further studies are required to determine the best process for inducing long-lasting change in behaviour in type 2 diabetic patients. The Diabetes Control and Complications Trial, which studied intensive management of type 1 diabetes, also reported post-intervention worsening, but this occurred 4 years after the intervention.…”
mentioning
confidence: 99%